An examination of the work history of Pittsburgh steelworkers, who were displaced and received publicly-funded retraining in the early 1980s - Robert W. Bednarzik; Joseph Szalanski (Institute for the Study of Labor (IZA), 2012)
A gap in the displaced worker-training literature is that the post-retraining period has not been studied over the long term. The approach here will be to examine in-depth the experience of a selected few displaced worker trainees over a 20 to 25 year period following their training. With our small sample, but in-depth examination, we will begin to remedy this gap in the literature. To understand better the training programs available for displaced steelworkers, we also interviewed people involved with the development and delivery of training. Further, when we discovered the grass roots growth of organizations to help displaced workers generally, we interviewed them as well. Our findings of the experience of 30 displaced steelworkers in Pittsburgh confirm those in the literature of training program attributes that increase the likelihood of their leading to a job. They include programs that are small scale, linked to the local job market, and focus on developing analytical skills. Two other key components perhaps helping account for the retraining success were assessment and auditing. Entrance into the training program required an intensive screening or assessment process to ensure that (1) the program was right for them, and (2), more importantly, they were capable of handling and grasping the content of the training. Helping displaced workers with tuition payments at a community college also has merit.
urn:nbn:de:101:1-201207125626
Keywords: J24; J68; 330; training; displaced workers; Metallberufe; Arbeitslosigkeit; Umschulung; Wirkungsanalyse; Berufliche Integration; USA